UPAYA PETUGAS ASSEMBLING UNTUK MELENGKAPI BERKAS REKAM MEDIS PASIEN RAWAT INAP DENGAN MENGGUNAKAN METODE KUALITATIF DI RUMAH SAKIT UNIVERSITAS SUMATERA UTARA - ROSALINA, YUDICA (JURNAL ILMIAH KOHESI, 2022)
Background: Assembling officers must make efforts to maintain the completeness of medical record files. By making these efforts, it is hoped that they can complete incomplete medical record files. at the University of North Sumatra Hospital. The results of interviews with the Head of Medical Records and Documentation Studies for inpatient medical record files revealed that this goal had not yet been achieved because incomplete inpatient medical record files were still found. Research Objective: to determine the efforts that can be made to maintain the completeness of medical record files. Research method: This type of research is descriptive research with a qualitative approach and a cross-sectional research design. The subjects in this research were assembling officers, two doctors, two nurses, and the head of the Medical Records agency. Data collection techniques are observation, interviews and documentation studies. Research Results: the causes of incomplete medical record files are a) Man: nurses prioritize service or treatment of patients; nurses still don't remind doctors of the parts of the medical record that must be filled in by the doctor, the doctor visits once a week; Doctors must immediately treat patients who need help. b) methods; the procedure for filling out medical record files has not been socialized to doctors or nurses. c) machines; There is no date stamp facility. e) Money; There is no incentive system if filling in medical records is still incomplete. Efforts to complete the medical record files for inpatient medical patients.